Representações do funk como proibidão e light: uma análise do discurso midiático em notícias do portal UOL - Manoel Ivany dos Santos Vieira Junior (2023)
This research is part of Critical Language Studies (CLS) more precisely Critical Discourse Analysis (CDA). The theme of this research is related to the representations of funk that are constructed and ideologically motivated through discourse, especially media discourse. More precisely, we are interested in investigating the way in which the media, based on news about funk music, constructs and reproduces representations of funk proibidão and funk light. Due to the fact that the theme of funk is controversial with regard to paradoxical issues, such as funk being discussed as a booster of social problems or as movement or cultural manifestation of the periphery (VIEIRA JUNIOR, 2020), this research seeks to analyze in two news published by the UOL portal in the year 2021, which categorize funk as proibidão and light, discourses that point out to two ways of representing funk, as well as to investigate the social implications of each representation. Thus, we seek the theoretical-methodological framework of CDA, through the perspective of Fairclough (1992; 2001), with his Dialectical-Relational approach, through concepts such as discourse, text, discursive practice and social practice. For our linguistic analysis, we use the Systemic-Functional Grammar (SFG), by Halliday and Matthiessen (2014), which conceives the sentence, according to the ideational metafunction in the experiential dimension, as representation. After our analysis, we confirmed the hypothesis that, in the media, especially in the news analyzed, there are two contrasting ways of representing funk, in effect, in society, generating dichotomous forms of the same social phenomenon: on one side, the proibidão funk as the one which lives in the favela, with shameless terms and marginalized, without space in civilized society; on the other side, funk light as the one that circulates more civilly or, at least, in a less controversial way, adapting to the precepts of hegemony and thus gaining more space in the media.